2021
DOI: 10.1021/acschemneuro.1c00192
|View full text |Cite
|
Sign up to set email alerts
|

Selective Fatty Acid Amide Hydrolase Inhibitors as Potential Novel Antiepileptic Agents

Abstract: Temporal lobe epilepsy is the most common form of epilepsy and current antiepileptic drugs are ineffective in many patients. The endocannabinoid system has been associated with an ondemand protective response to seizures. Blocking endocannabinoids' catabolism would elicit antiepileptic effects, devoid of psychotropic effects. We herein report the discovery of selective anandamide catabolic enzyme fatty acid amide hydrolase (FAAH) inhibitors with promising antiepileptic efficacy, starting from a further investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 90 publications
0
17
0
Order By: Relevance
“…In the last few years, academic and industrial efforts have been strongly focused on the development of selective FAAH or MAGL inhibitors with potential therapeutic application in several diseases such as MS, epilepsy, neuropathic pain, and chronic pain disorders [86,144,[154][155][156]. However, the simultaneous inhibition of the two main ECS catabolic enzymes also appears as a promising therapeutic strategy.…”
Section: Dual Faah-magl Inhibitorsmentioning
confidence: 99%
“…In the last few years, academic and industrial efforts have been strongly focused on the development of selective FAAH or MAGL inhibitors with potential therapeutic application in several diseases such as MS, epilepsy, neuropathic pain, and chronic pain disorders [86,144,[154][155][156]. However, the simultaneous inhibition of the two main ECS catabolic enzymes also appears as a promising therapeutic strategy.…”
Section: Dual Faah-magl Inhibitorsmentioning
confidence: 99%
“…63 Previous research has shown that FAAH inhibitors can reduce the oxidative state by reducing the DNAbinding activity of NF-κB p65 without cytotoxicity. 64 Our results showed that both genetic and pharmacological inhibition of FAAH could inhibit RANKL-induced NF-κB and MAPK signaling pathways, suggesting that FAAH inhibition can suppress RANKL-induced osteoclast differentiation by inhibiting NF-κB and MAPK pathways activation. It is worth noting that the process of signal transduction is transient, the expression of signaling molecules increased rapidly after stimulation, reached a peak at about 15 min, and then quickly decreased.…”
Section: Discussionmentioning
confidence: 52%
“…Solubility and chemical stability have been determined at 25 °C using HPLC protocol, as previously reported by us [42,48] . Briefly, a Chromolith HPLC column RP‐18 was employed.…”
Section: Methodsmentioning
confidence: 99%
“…Solubility and chemical stability have been determined at 25 °C using HPLC protocol, as previously reported by us. [42,48] Briefly, a Chromolith HPLC column RP-18 was employed. The analysis were performed at 25 °C using a gradient elution mixture of MeCN/H 2 O (with 0.1 % TFA as the phase modifier) starting from a 0 % to 20 % MeCN in 4 min and then up to 50 % MeCN in 3 min with flow speed of 0.8 mL/min.…”
Section: Solubility and Chemical Stability Assaysmentioning
confidence: 99%